Peran Orang Tua Dalam Meminimalkan Dampak Hospitalisasi Pada Anak Prasekolah: Studi Literatur - Intan Rukmana; Ema Arum Rukmasari; Indra Maulana (Universitas Malahayati Lampung, 2022)
ABSTRACT Hospitalization causes anxiety, stress, loss of control, and body injury/pain in preschoolers. So the role of parents is needed to minimize the impact of hospitalization on children, so there is a need for a literature study to review the role of parents in minimizing the impact of hospitalization on preschool children. The purpose of this literature study was to identify the role of parents in minimizing the impact of hospitalization on preschool children. Method This literature study used the results of a database search. The strategy used to search for literature used Google Scholar for as many as 47 articles, Pudmed for as many as 6 articles, Proquest for as many as 1 articles, PeerJ for as many as 2 articles, and Plos for as many as 4 articles with article inclusion criteria using the Cross-Sectional approach method, full-text articles, preschool children, publication year (2010-2020), the role of parents and the impact of hospitalization. Based on the inclusion criteria, 10 articles were analyzed using the Synthesis Matrix. Result Based on a review of 10 articles that had been analyzed, the impact of hospitalization was anxiety about separation from parents, loss of control, body injury/pain, and stress, with the highest distribution of anxiety levels. The role of people was to provide good care as long as the child was hospitalized with love, comfort, safety, support, motivation, and calm. From 5 articles that explained the role of parents in the impact of hospitalization on children, parents could make children calmer because they lived together and met the children's needs during hospitalization. Parents worked closely with nurses during the procedure to help children minimize the impact of hospitalization during treatment. From all articles that had been analyzed, there were 4 impacts of hospitalization, namely anxiety, loss of control, body injury/pain, and stress. So the role of parents given to children will affect children, a good role will be given by parents to children to reduce the risk of the impact of hospitalization, as well as nurses as caregivers who will provide good care during hospitalization. Keywords: Preschool Children, Impact of Hospitalization, The role of parents ABSTRAK Hospitalisasi mengakibatkan kecemasan, stress, kehilangan kontrol, dan cedera tubuh/nyeri pada anak prasekolah. Maka peran orang tua dibutuhkan untuk meminimalkan dampak hospitalisasi pada anak sehingga perlu adanya kajian literature review terhadap peran orang tua dalam meminimalkan dampak hospitalisasi pada anak prasekolah. Tujuan studi literatur ini adalah untuk mengidentifikasi peran orang tua dalam meminimalkan dampak hospitalisasi pada anak prasekolah. Metode Studi Literatur menggunakan studi literature review dari hasil pencarian database. Stategi yang digunakan untuk mencari literature menggunakan Google Scholar sebanyak 47 artikel, Pudmed sebanyak 6 artikel, Proquest sebanyak 1 artikel, PeerJ sebanyak 2 artikel , dan Plos sebanyak 4 artikel dengan kriteria inklusi artikel yang menggunakan metode pendekatan Cross Sectional, artikel full teks, anak prasekolah, tahun terbit (2010-2020), artikel peran orang tua dan dampak hospitalisasi. Berdasarkan kriteria inklusi didapatkan 10 artikel yang akan dianalisis menggunakan Matrix Sintesis. Hasil Berdasarkan review dari 10 artikel yang telah di analisis bahwa dampak hospitalisasi ada kecemasan akan perpisahan dengan orang tua, kehilangan kontrol, cedera tubuh/nyeri, dan stress, dengan distribusi tertinggi tingkat kecemasan. Peran orang memberikan perawatan yang baik selama anak dihospitalisasi dengan kasih sayang, kenyamanan, keamanan, dukungan, motivasi dan ketenangan. Dari 5 artikel yang menjelaskan peran orang tua dengan dampak hospitalisasi pada anak, orang tua bisa membuat anak menjadi lebih tenang karena tinggal bersama dan memenuhi kebutuhan anak selama hospitalisasi. Orang tua bekerja sama dengan perawat selama tindakan berlangsung sehingga membantu anak dalam meminimalkan dampak hospitalisasi selama perawatan. Dari seluruh artikel yang telah dianalisis maka dampak hospitalisasi ada 4 yaitu kecemasan, kehilangan kontrol, cedera tubuh/nyeri, dan stress. Maka peran orang tua yang diberikan kepada anak akan berpengaruh pada anak, peran yang baik akan diberikan oleh orang tua pada anak untuk mengurangi resiko dampak hospitalisasi, begitupun perawat sebagai care giver yang akan memberikan perawatan baik selama hospitalisasi. Kata Kunci: Anak Prasekolah, Dampak Hospitalisasi, Peran orang tua